Effect of Epigallocatechin-3-gallate (EGCG) on cell proliferation inhibition and apoptosis induction in lymphoblastic leukemia cell line - Ghasemi-Pirbaluti Masome; Pourgheysari Batool; Shirzad Hedayatollah; Motaghi Ehsan; Askarian Dehkordi Narges; Surani Zahra; Shirzad Moein; Beshkar Pezhman; Pirayesh Ashkan (Shahrekord University of Medical Sciences, 2015)
Introduction: Acute lymphoblastic leukemia (ALL) is one of the malignant proliferations of lymphoid cells in the early stages of differentiation and accounts for ¾ of all cases of childhood leukemia. Available treatment cannot completely treat this disease. Epigallocatechin-3-gallate (EGCG) is a polyphenolic compounds in the green tea that has demonstrated to have anticancer and antimitotic properties. The purpose of the present study was the evaluation of the effect of EGCG on the proliferation inhibition and apoptosis induction in a lymphoblastic leukemia cell line. Methods: Jurkat cell line was cultured in standard condition and in different concentrations of EGCG (0-100 micromolar) for 24, 48 and 72 hours. Cell viability was measured by MTS assay. Apoptosis induction was assessed by annexin V-FITC and flow cytometry analysis. Results: The MTS assay revealed that EGCG has decreased cell viability with a time and dose dependent manner. The level of cell apoptosis in all used concentrations of EGCG (50, 70 and 100 μm) was higher than control group (71%, 40% and 31% respectively vs. 8%) and reached to significant level at 100 μm concentration. Conclusion: The study indicated that EGCG is effective on proliferation inhibition and apoptotic induction in Jurkat lymphoblastic cell line. Therefore, the study of the mechanism of apoptosis induction could be a step of progress toward target therapy which might be considered in the future studies.